2018
DOI: 10.1016/j.ajog.2018.01.026
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of fetal heart rate monitoring: deceleration area is predictive of fetal acidemia

Abstract: Deceleration area is the most predictive electronic fetal monitoring pattern for acidemia, and combined with tachycardia for significant risk of morbidity, from the electronic fetal monitoring patterns studied. It is important to acknowledge that this study was performed in patients delivering ≥37 weeks, which may limit the generalizability to preterm populations. We also did not use computerized analysis of the electronic fetal monitoring patterns because human visual interpretation was the basis for the Euni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 47 publications
(39 reference statements)
10
119
3
1
Order By: Relevance
“…An optimal cut‐off value of total deceleration area using the Youden index gained an NNT (number needed to treat) of five cesareans to prevent one case of acidemia. In the study, there was no differentiation between variable and late decelerations .…”
Section: Discussionmentioning
confidence: 63%
“…An optimal cut‐off value of total deceleration area using the Youden index gained an NNT (number needed to treat) of five cesareans to prevent one case of acidemia. In the study, there was no differentiation between variable and late decelerations .…”
Section: Discussionmentioning
confidence: 63%
“…taking into account the depth, duration and frequency of all decelerations) shows the best association with fetal acidaemia (Cahill et al . ). Impressively, this study suggested that the sole use of total deceleration area would be associated with five Caesareans needing to be performed to prevent one case of acidaemia (Cahill et al .…”
Section: Introductionmentioning
confidence: 97%
“…Impressively, this study suggested that the sole use of total deceleration area would be associated with five Caesareans needing to be performed to prevent one case of acidaemia (Cahill et al . ). This and similar studies have highlighted the superior clinical utility of assessing decelerations in a physiologically relevant manner, in contrast to the historical focus on timing (Cahill et al .…”
Section: Introductionmentioning
confidence: 97%
“…Exclusion criteria and detailed methods of the parent study have been previously described. 5 Briefly, obstetric research nurses were formally trained to review EFM patterns systematically using the National Institute of Child Health and Human Development criteria 6 and were blinded to all clinical data. EFM data were extracted in 12 10-minute epochs.…”
Section: Methodsmentioning
confidence: 99%